The acidic microenvironment in the perisinusoidal space critically determines bile salt-induced activation of hepatic stellate cells - Jingguo Li; Shun Yao; Sebastian Zimny; Dennis Koob; Hai Jin; Ralf Wimmer; Gerald Denk; Biguang Tuo; Simon Hohenester (Communications Biology)
Abstract Cholestatic liver diseases, accompanied by the hepatic accumulation of bile salts, frequently lead to liver fibrosis, while underlying profibrogenic mechanisms remain incompletely understood. Here, we evaluated the role of extracellular pH (pHe) on bile salt entry and hepatic stellate cell (HSC) activation and proliferation. As modulators of intracellular pH (pHi), various proton pump inhibitors (PPI) were tested for their ability to prevent bile salt entry and HSC activation. Lastly, the PPI pantoprazole was employed in the 3,5-Diethoxycarbonyl-1,4-Dihydrocollidine (DDC)-diet model of cholestatic liver fibrosis. We found in vitro, that slightly acidic pHe (7.2–7.3) enhanced bile salt accumulation in HSC and was a prerequisite to bile salt-induced HSC activation. Pantoprazole in the DDC model exhibited antifibrotic effects. We conclude that bile salt-induced activation of HSC may depend on the slightly acidic microenvironment present in the perisinusoidal space and modulation of pHi in HSC may offer a novel pharmacological target in cholestatic disease.